Foliar Spray of Nitrogen Fertilizer on Raised Bed Increases Yield of Transplanted Aman Rice over Conventional Method. (20th November 2012) - Bhuyan, M. H. M.; Ferdousi, Mst. R.; Iqbal, M. T.
Abstract : Bed planting with foliar nitrogen fertilizer application of rice production systems is very new, and research on it is still at introductory phase. Influence of foliar application of nitrogen fertilizer on growth and yield of transplanted aman rice and evaluation of water and fertilizer application efficiency of rice-fallow-rice cropping system were investigated under raised bed cultivation method. Results showed that foliar spray in bed planting method increased grain yield of transplanted aman rice up to 9.33% over conventional method. Foliar nitrogen fertilizer application in bed planting method increased the number of panicle m −2, number of grains panicle −1, and 1000-grain weight of rice than the conventional method. Sterility percentage and weed infestation were lower at foliar nitrogen fertilizer application in bed planting method than the conventional method. Thirty-nine percent of irrigation water and time for application could be saved through foliar nitrogen spray in bed planting than conventional method. Water use efficiency for grain and biomass production was higher by foliar nitrogen fertilizer application in bed planting than conventional method. Likewise, agronomic efficiency of foliar nitrogen fertilizer application in bed planting method was higher than the conventional method. This study concluded that foliar nitrogen spray in bed planting method is a new approach to get fertilizer and water use efficiency as well as higher yield compared to existing agronomic practice in Bangladesh.